Replacement names for Cyrtandra humilis Elmer and Cyrtandra umbellata Kraenzl., two endemic Philippine species (Gesneriaceae) - Olivar, Jay Edneil C.; Muellner-Riehl, Alexandra (Phytotaxa, 2019)
Cyrtandra Forster & Forster (1776: 5) is the largest genus in the family Gesneriaceae, with over 800 species distributed throughout Southeast Asia and the Pacific (Atkins et al. 2013). Members of the genus are important understory elements in primary forests, with varying habits (Burtt 2001). The Philippines is considered a center of diversity for the genus, with approximately 105–150 spp. (Atkins et al. 2013, Johnson et al. 2017).